Developing a conceptual model of geomorphic change for channel management proposes: a case of Langat River basin - Mohd Ekhwan Hj. Toriman, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2008)
This article examines channel changes using predictive model of geomorphic change in the Langat River catchment. River geomorphic change resulted from a number of variables control such as climate, geology, water discharge, sediment influx, the bed and bank characteristics, vegetation covers and human interference. Three variables found to be satisfied to develop the dynamic model of geomorphic change in the Langat River catchment namely channel flow regime, channel competence and catchment sediment production (QMAG, QVAR, SEDO, COMP). These computer-generated of conceptual model provides the basis forms to which any particular section of Langat River could be change as demonstrate by flow levels, morphological units and frequency of inundation linkages model in the selected section of Langat River. The model found to be useful in providing the information whereby morphology, local and regional hydraulic conditions can be discussed, described and quantifies. It also can be act as an alternative to river management system to guide planners and engineers involved in the management of the river or its surrounding corridor